L’osteosintesi nelle fratture periprotesiche di ginocchio: una chirurgia difficile - Solarino, G.; Vicenti, G.; Carrozzo, M.; Mori, C.M.; Moretti, B. (Lo Scalpello - Journal, 2018)
OSTEOSYNTHESIS OF PERIPROSTHETIC FRACTURES FOLLOWING TOTAL KNEE ARTHROPLASTY: A CHALLENGING SURGERYThe incidence of periprosthetic fractures after total knee arthroplasty appears to be on the rise as a result of theincreasing longevity of patients with knee prosthetic implants. The most common pattern involves the supracondylararea of the distal femur above a well-fixed prosthesis. If a periprosthetic fracture occurs, an appropriate treatmentmethod should be selected considering different factors.